Pemanfaatan Air Waduk Menjadi Suplai Air Bersih bagi Masyarakat (Sebuah Aksi Parsipatorif Mengatasi Kebutuhab Air Bersih di Dusun Amburan Desa Kandangan Cerme Gresik Jawa Timur) - Chairudin, Mochamad (Proceedings of Annual Conference on Community Engagement, 2022)
Amburan hamlet consists of 70% agriculture and 25% settlements and 5% in the form of reservoirs. This area has water shortages during the dry season, the land becomes dry and arid, water sources are difficult to find while in the rainy season water is very abundant. Reservoir as a foundation for people to look for clean water during the dry season. Armed with water carts, the community carried water from the reservoir to their homes. Assistance-based research aims to raise awareness for the use of reservoir water as a clean water supply. By applying the Asset Based Community Development (ABCD) method by involving various parties, it is expect to provide optimal changes and benefits.